Evaluation of Entamoeba histolytica recombinant phosphoglucomutase protein for serodiagnosis of amoebic liver abscess - Ning, Tan Zi (BioMed Central, 2013)
BACKGROUND: Amoebic liver abscess (ALA) is the most frequent clinical presentation of extra-intestinal amoebiasis. The diagnosis of ALA is typically based on the developing clinical symptoms, characteristic changes on radiological imaging and serology. Numerous serological tests have been introduced for the diagnosis of ALA, either detecting circulating amoebic antigens or antibodies. However those tests show some pitfalls in their efficacy and/or the preparation of the tests are costly and tedious. The commercial IHA kit that used crude antigen was reported to be useful in diagnosis of ALA, however high antibody background in endemic areas may cause problems in its interpretation. Thus, discovery of well-defined antigen(s) is urgently needed to improve the weaknesses of current serodiagnostic tests. METHODS: Crude antigen of E. histolytica was analysed by 2-DE and Western blot to identify a protein of diagnostic potential for ALA. The corresponding gene of the antigenic protein was then cloned, expressed and the purified recombinant protein was subsequently evaluated for serodiagnosis of ALA in an indirect ELISA format. RESULTS: Analysis of crude antigen showed that phosphoglucomutase (PGM) has the diagnostic potential. Recombinant PGM (rPGM) showed 79.17% (19/24) sensitivity and 86.67% (195/225) specificity in diagnosis of ALA based on the COV of mean +1SD. There was no significant difference between rPGM-ELISA and IHA diagnostic kit in the diagnosis of ALA in terms of sensitivity and specificity at p-value < 0.05. CONCLUSION: In conclusion, rPGM-ELISA is found to be useful for serodiagnosis of ALA. Future studies will determine whether rPGM-ELISA also detects antibodies produced in amoebic dysentery and asymptomatic cases.